TRILOGI SISTEM PENDIDIKAN PESANTREN MUHAMMADIYAH: SUATU PENGANTAR - Ichwansyah Tampubolon (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Abstract: PontrenMu has three patterns of Islamic education system, namely: the madrasa system, the Islamic Boarding School system, and expertise (takhaşşsuş) system. The madrasa system is a model of modernization of Islamic traditional educational system and Islamic Boarding School system seems as a model of “postmodernized” high school (sekolah) educational system. Meanwhile, expertise (takhaşşsuş) system can be called as a neo-postmodernized Islamic Boarding School system in which the graduate Islamic educational system integrating with traditional Islamic education in a spesific pattern (pesantren luhur/ma`had `aly). All of that Islamic educational systems are oriented to realize the vision and mission of Muhammadiyah in order to produce the cadres of ulema-intellectual or intellectual-ulema formally and simultaneously. Besides of being the alternative strategies for improvement of Islamic educational system of Muhammadiyah in both levels of high and graduate school, the three patterns of Islamic education system are also being solutions for fulfillment of demands and needs of Moslem communities in contemporary era. Key words: PontrenMu education system, madrasa, Islamic Boarding System, expertise (takhaşşsuş)